2022
DOI: 10.48550/arxiv.2205.05709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Another Shipment of Six Short-Period Giant Planets from TESS

Abstract: We present the discovery and characterization of six short-period, transiting giant planets from NASA's Transiting Exoplanet Survey Satellite (TESS) -TOI-1811 (TIC 376524552), TOI-2025 (TIC 394050135), TOI-2145 (TIC 88992642), TOI-2152 (TIC 395393265), TOI-2154 (TIC 428787891), & TOI-2497 (TIC 97568467). All six planets orbit bright host stars (8.9 < G < 11.8, 7.7 < K < 10.1). Using a combination of time-series photometric and spectroscopic follow-up observations from the TESS Follow-up Observing Program (TFOP… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…We have confirmed and characterized 20 new short-period giant planets detected by the TESS mission, based on extensive ground-based photometric, spectroscopic, and imaging observations. These objects join a host of other giant planets that have been discovered by TESS over the last few years (e.g., Rodriguez et al 2019;Zhou et al 2019;Brahm et al 2020;Davis et al 2020;Nielsen et al 2020;Ikwut-Ukwa et al 2021;Rodriguez et al 2021;Sha et al 2021;Wong et al 2021;Knudstrup et al 2022;Psaridi et al 2022;Rodriguez et al 2022;Yee et al 2022), showcasing how TESS is rapidly transforming our knowledge of hot Jupiters by providing a uniform, all-sky sample of these planets. Yee et al (2021) found that the sample of known transiting hot Jupiters was only ∼40% complete at a magnitude-limit of G < 12.5.…”
Section: Discussionmentioning
confidence: 99%
“…We have confirmed and characterized 20 new short-period giant planets detected by the TESS mission, based on extensive ground-based photometric, spectroscopic, and imaging observations. These objects join a host of other giant planets that have been discovered by TESS over the last few years (e.g., Rodriguez et al 2019;Zhou et al 2019;Brahm et al 2020;Davis et al 2020;Nielsen et al 2020;Ikwut-Ukwa et al 2021;Rodriguez et al 2021;Sha et al 2021;Wong et al 2021;Knudstrup et al 2022;Psaridi et al 2022;Rodriguez et al 2022;Yee et al 2022), showcasing how TESS is rapidly transforming our knowledge of hot Jupiters by providing a uniform, all-sky sample of these planets. Yee et al (2021) found that the sample of known transiting hot Jupiters was only ∼40% complete at a magnitude-limit of G < 12.5.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the forecast of Yee et al (2021), to assemble a sample of 400 hot Jupiters (an order of magnitude more planets than the Kepler sample), a magnitude-limited survey would need to be complete down to G = 12.5. The 10 planets described here, along with the other new TESS hot Jupiters that have been described in the literature (e.g., Rodriguez et al 2019;Zhou et al 2019;Brahm et al 2020;Davis et al 2020;Nielsen et al 2020;Ikwut-Ukwa et al 2021;Rodriguez et al 2021;Sha et al 2021;Wong et al 2021;Knudstrup et al 2022;Rodriguez et al 2022) are steps toward realizing the promise of TESS for hot Jupiter demographics. Note.…”
Section: Discussionmentioning
confidence: 99%
“…We have confirmed and characterized twenty new short-period giant planets detected by the TESS mission, based on extensive ground-based photometric, spectroscopic, and imaging observations. These objects join a host of other giant planets that have been discovered by TESS over the last few years (e.g., Rodriguez et al 2019;Zhou et al 2019;Brahm et al 2020;Davis et al 2020;Nielsen et al 2020;Ikwut-Ukwa et al 2021;Rodriguez et al 2021;Sha et al 2021;Wong et al 2021;Knudstrup et al 2022;Rodriguez et al 2022;Psaridi et al 2022;Yee et al 2022), showcasing how TESS is rapidly transforming our knowledge of hot Jupiters by providing a uniform, all-sky sample of these planets. Yee et al (2021) found that the sample of known transiting hot Jupiters was only ∼ 40% complete at a magnitude-limit of G < 12.5.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the forecast of Yee et al (2021), to assemble a sample of 400 hot Jupiters (an orderof-magnitude more planets than the Kepler sample), a magnitude-limited survey would need to be complete down to G = 12.5. The ten planets described here, along with the other new TESS hot Jupiters that have been described in the literature (e.g., Rodriguez et al 2019;Zhou et al 2019;Brahm et al 2020;Davis et al 2020;Nielsen et al 2020;Ikwut-Ukwa et al 2021;Rodriguez et al 2021;Sha et al 2021;Wong et al 2021;Knudstrup et al 2022;Rodriguez et al 2022) are steps toward realizing the promise of TESS for hot Jupiter demographics.…”
Section: Discussionmentioning
confidence: 99%